Noise Cancellation Studies in Vectoring DSL Technologies - Mohd Yasir, Siti Sarah Rahimah; Ramli, Khairun Nidzam; Che Seman, Fauziahanim (Evolution in Electrical and Electronic Engineering, 2021)
Vectoring is one of the extensions of Digital Subscriber Line (DSL) technologies that utilize the concept of noise cancellation in its system where the technology analyses noise on copper lines and creates inverted noise so that they would be cancelling each other. This concept is proved to be effective and cost-friendly. In this thesis, noise cancellation in vectoring DSL technologies is studied by acquiring the data through laboratory setup. The cable length of 100 m to 1000 m is used, to indicate the real situation for the customer premises where their location varies. We also compare the results when 3 modems are used and when 6 modems are used. Different traffic conditions from low, medium to high is also being considered in the measurement as we use Ixia Ixchariot to indicate user activities. The performance of the network is compared and discussed through the attainable data rate, line data rate, line attenuation and FEC error. Each data is correlated and discussed with each other in different configurations. Noise cancellation effectiveness is studied from the relationship of FEC error and line rate. From the results, we managed to observe the attainable rate, line rate, attenuation and FEC error performances over distance.  We also could see the effectiveness of noise cancellation as it helps the modem to maintain its speed even when the FEC error is high.